Modelling the aerodynamics of an aero-engine exhaust system - Al-Akam, Aws Akram Mahmood (Cranfield University, 2018)
Aero-engine design is one of the most demanding tasks when the aircraft is constructed. The selection of the engine component’s size and geometrical features depends on the assurance that the losses are minimal. The exhaust system is one of the main components that noticeably affect the overall propulsion-system performance because of its central role in the thrust production. Thus, it is essential to have an accurate performance assessment of the exhaust system in early design stages of the engine. However, to select the adequate design, a wide range of geometrical configurations of the exhaust system has to be covered. This task will increase the production cost and the time occupied during the construction of the engine. Therefore, it is essential to produce an evaluation tool can calculate the engine performance accurately, before making a commitment to the final design. This research aims to generate a tool that predicts aero-engine performance during the preliminary design stages, with high sensitivity to the effect of the geometrical parameterisation of the exhaust system. To achieve this aim, a high fidelity assessment model for the exhaust-system performance was developed employing computational fluid dynamics method. This model was utilised to build a high degree of freedom maps of the performance metrics of a basic nozzle configuration (with a plug). These maps cover a range of geometrical parameters, in terms of the nozzle contraction ratio (CR) (the ratio of the nozzle charging area to the nozzle throat area) and the plug half-angle, alongside with the variation in the nozzle pressure ratio. Furthermore, correction factors were produced to take into account the impact of the bypass nozzle jet on the core nozzle performance. The aerodynamic interference effect between the wing and the exhaust system was also considered by correcting the engine net thrust. This was achieved by generating correction factors to the nozzle gross-thrust as a function of the engine position and the local static pressure. The derived nozzle performance maps were used to improve the calculations for a non-dimensional engine performance model, utilising response surface methods. Furthermore, the installation correction factors were employed to recalculate the performance data of an installed engine. Through the use of the modified performance model of the engine, a 4.0% improvement was observed in the engine’s gross thrust, and reduction in the specific fuel consumption by 10%, for a high-bypass-ratio engine runs under typical cruise conditions. Moreover, the effect of the wing pressure field on the exhaust-system improved the engine net thrust by a range of 2.3% at the start of the cruise and 2.1% at the end of the cruise segment. However, the net propulsive force of the engine was lower than the net thrust by a range of 0.28% to 0.6% across the cruise segment, despite the improvement in the exhaustsystem performance. The results of this project show the importance and suitability of building an assessment model of the nozzle performance and use it to improve the engine thrust calculations. They, also, highlight the discrepancies because of the simplifications in previous nozzle characteristic representations and the installed engine performance calculations.
Keywords: Propelling-nozzle; nozzle performance metrics; nozzle parameterisation; engine-aircraft aerodynamic interference